MENGUKUR KINERJA PERPUSTAKAAN - Sri Purnomowati (BACA: Jurnal Dokumentasi dan Informasi, 2000)
The purpose of this article is to discuss library performance measurement and introduce the ISO 11620-1998 which contain 29 library performance indicators. It is different with the library statistic which usually focus on input/output measurement, the library performance measurement is focused more on efficiency, effectiveness, cost-effectiveness and impact. Many factors should be considered in selecting performance indicators. There are many constraints in measuring the library performance, such as: human resources capability, data collection, definition ofthe population to be served for particular library, and choosing the appropriate indicators for Indonesian libraries.